Relationship between levels of beta-carotene, vitamin A and vitamin E in the seminal plasma, spermatozoa, blood serum and liver of rainbow trout - Naziroglu, M; Gür, S; Simsek, H; Köprücü, K (Wiley, 2000)
[Abstract Not Available]
Keywords: Selenium; Semen; Peroxidation; Antioxidant; Tocopherol